Analisis Wacana Kritis Media dalam Pemberitaan Peristiwa Kerusuhan Mahasiswa Papua di Surabaya - Pranata, Rian Pandi; Rohmad, Ahmad Khubby Ali; Umam, Moh. Khoirul (Prodi Sosiologi, Fakultas Ilmu Sosial dan Ilmu Politik, UIN Sunan Ampel Surabaya, 2024)
This research employs critical discourse analysis of media to examine the news coverage of the Papua student riot in Surabaya. This study analyzes how media texts and narratives apply news coverage of the incident in the Papuan Student riots in Surabaya. This study adopts a qualitative descriptive approach, utilizing Norman Fairclough's Critical Discourse Analysis as its analytical framework. Data collection methods include observation and documentation. The findings of this study indicate that the media's amplification of the Papua student riots in Surabaya reflects historical factors, situational konteks, and the hegemony of media institutions, leading to interpretative insinuation in news narratives that tend toward media-driven judgment. This tendency is reflected in headlines such as